Waffer industry residue in diets for Nile tilapia (Oreochromis niloticus) (Research, Society and Development, 2022)
Using alternative sources of food in animal nutrition is an effective way to avoid waste and reduce costs. The objective of this study was to evaluate the performance, heterogeneous growth and economic viability of Nile tilapia (Oreochromis niloticus) fingerlings, fed different levels of waffer biscuit residue in the diet (RB). A total of 100 fingerlings with initial weight of 3.0 ± 0.5 g were used, distributed in 20 aquaria of 70L, consisting of a system of recirculation of water and biofilter, during a period of 60 days. The animals were fed three times for day, until apparent satiety and were arranged in a completely randomized design, consisting of four treatments (0, 7, 14 and 21% addition of RB in the diet) and five replicates each. The fish fed with 14% and 21% RB in the ration presented better homogeneity in the growth. In addition, animals fed with 21% RB in the diet obtained better performance and economic viability. Therefore, it is recommended to use 21% RB in rations for Nile tilapia.